Micropropagação e análises bioquímicas e fitoquímicas de Physalis peruviana L. - Mascarenhas, Lilian Marcia Santana (2018)
Physalis peruviana L. (Solanaceae) is a fruit herbaceous, which has been consolidating in the small fruit market due to its nutritional, medicinal potentialities and relevant concentration of vitamins, minerals and secondary metabolites of interest to the pharmaceutical industry. The barriers to its production are the short reproductive cycle, the involvement of the fruits by pests and the lack of studies for the species. Micropropagation is an alternative for the propagation of medicinal species, since this technique allows the production of a large number of seedlings with phytosanitary quality, besides being a tool for genetic improvement and for phytochemical studies. This study aims to evaluate the in vitro morphogenesis of P. peruviana and to analyze the biochemical and phytochemical profile of the species in different cultures. Cotyledon node, cotyledon, leaf, epicotyl, hypocotyl and root explants were inoculated in half-saline MS culture medium supplemented with BAP (0,00; 2,22; 4,44; 6,66 and 8,88µM), plus 30 gL-1 of sucrose and 7 gL-1 of agar; and the explant cotyledonary node was submitted to (0,00; 2,22; 4,44; 6,66; 8,88; 13,32; 17,76 and 22,20 μM), plus 30 gL-1 of sucrose and 7 gL-1 of agar. It was verified that the cotyledon node submitted to the concentration of 12,50 μM BAP is the best source of explant, with regeneration of the shoots via direct organogenesis, and the leaf is the most efficient explant for the indirect organogenesis in concentrations of 4,44 μM BAP. Histological analysis proved the pathways of regeneration. The shoots from the direct organogenesis were rooted in vitro in MS½ medium free of plant regulator, and the microplants acclimatized in vegetal soil, reached 100% survival at 90 days of acclimatization. Biochemical and phytochemical analyzes of stem, root and leaf explants were carried out in vitro and ex vitro. The analysis showed that in vitro cultivation favors the synthesis of proteins and reducer sugars in leaf and root tissues. The metabolite rutin is produced in leaf explants in greenhouse.